Simulation of channeling contrast in scanning ion microscope images - Kaoru Ohya (AIP Advances, 2018)
The scanning ion microscope (SIM) provides a distinct channeling contrast in backscattered ion (BSI) and secondary electron (SE) images owing to its wide critical angle for ion channeling. In this report, we present a molecular dynamics (MD) simulation of a crystalline sample’s channeling contrast that has been scanned by ion beams of 30 keV He, Ne, and Ga in the SIM. A middle portion of the sample surface inclined at different angles against neighboring sides oriented toward the ions’ channeling direction. Line profiles of the BSI and SE yields along the surface reproduced crystalline-oriented changes that are expected for a transparency model. Nevertheless, a trajectory simulation of the ions in the sample according to the MD technique suggests some contrast differences from that of the model for the BSI and SE images and for different ion species.